2009
DOI: 10.2202/1548-923x.1635
|View full text |Cite
|
Sign up to set email alerts
|

Keeping the Vision: Sustaining Social Consciousness with Nursing Students following International Learning Experiences

Abstract: In an era of globalization, increasing numbers of nursing programs are initiating international learning experiences, yet empirical data is lacking regarding long term benefits and effects of international placements. This paper presents findings from a participatory action study designed in response to this gap. Objectives were to describe student learning in international experiences, and to facilitate strategies that supported integration of this learning into personal and professional domains upon return t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Many nursing programs in North America offer an international clinical placement 1 as part of the undergraduate nursing program (Bosworth et al, 2006;Hanson, 2010;Reimer Kirkham, Van Hofwegen, & Pankratz, 2009;SmithMiller, Leak, Harlan, Dieckmann, & Sherwood, 2010). The popularity of these types of experiences has grown substantially within the last decade, often driven by the needs or desires of the student population (Levi, 2009;Wehbi, 2009;Yudkin, Bayley, Elnour, Willott, & Miranda, 2003).…”
mentioning
confidence: 99%
“…Many nursing programs in North America offer an international clinical placement 1 as part of the undergraduate nursing program (Bosworth et al, 2006;Hanson, 2010;Reimer Kirkham, Van Hofwegen, & Pankratz, 2009;SmithMiller, Leak, Harlan, Dieckmann, & Sherwood, 2010). The popularity of these types of experiences has grown substantially within the last decade, often driven by the needs or desires of the student population (Levi, 2009;Wehbi, 2009;Yudkin, Bayley, Elnour, Willott, & Miranda, 2003).…”
mentioning
confidence: 99%
“…Canadian nursing students who participated in an immersion experience in a Guatemalan community was also studied using a descriptive approach (Reimer-Kirkham, Van Hofwegen, & Pankratz, 2009). The nursing students lived among Guatemalan residents and collaborated with the Guatemalan community health clinic nurse to conduct health screenings and health fairs.…”
Section: Transcultural Immersionmentioning
confidence: 99%
“…A questionnaire with open-ended questions was designed based on themes derived from the literature review and earlier studies (a qualitative study and a national survey) eliciting information from students and educators regarding innovative clinical placements (Hoe Harwood et al, 2009;Reimer-Kirkham et al, 2005;Reimer-Kirkham et al, 2009). Questions included: "How do you decide whether to take student placements?…”
Section: Describing the Studymentioning
confidence: 99%
“…The survey reported that Canadian nurse educators rely upon student placements such as correctional facilities, Aboriginal communities, international placements, rural and parish settings; reports that are corroborated in other regions (Sloan, Keely, & Groves, 2008;Stewart, 2007). Student learning in these community-based settings has been described as transformative, with students gaining enhanced critical thinking competencies (Pijl-Zieber & Kalischuk, 2011;ReimerKirkham et al, 2005;Reimer-Kirkham, Van Hofwegen, & Pankratz, 2009). Despite this widespread reliance on alternative placements and the reports of transformative learning, few studies have reported the host agency perspective.…”
Section: Introductionmentioning
confidence: 99%